2022
DOI: 10.1007/s00018-022-04379-y
|View full text |Cite
|
Sign up to set email alerts
|

Maternal gut microbiota Bifidobacterium promotes placental morphogenesis, nutrient transport and fetal growth in mice

Abstract: The gut microbiota plays a central role in regulating host metabolism. While substantial progress has been made in discerning how the microbiota influences host functions post birth and beyond, little is known about how key members of the maternal gut microbiota can influence feto-placental growth. Notably, in pregnant women, Bifidobacterium represents a key beneficial microbiota genus, with levels observed to increase across pregnancy. Here, using germ-free and specific-pathogen-free mice, we demonstrate that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 74 publications
2
37
0
Order By: Relevance
“…Maternal gut microbiota could affect maternal and placental metabolome (i.e. acetate, formate and carnitine), and then promote placental morphogenesis, nutrient transport and fetal growth in mice ( 18 ). We indeed observed that normal sows had significantly higher concentration of SCFAs in feces than sows giving birth to stillborn piglets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal gut microbiota could affect maternal and placental metabolome (i.e. acetate, formate and carnitine), and then promote placental morphogenesis, nutrient transport and fetal growth in mice ( 18 ). We indeed observed that normal sows had significantly higher concentration of SCFAs in feces than sows giving birth to stillborn piglets.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, intake of high-fat diet could result in placental hypoxia which impaired the development of the fetus ( 17 ). Bifidobacterium in maternal gut microbiota promotes placental morphogenesis, nutrient transport and fetal growth in mice ( 18 ). By far, whether the alteration of gut microbiota causes the occurrence of stillborn piglets in sows has still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Protein abundance was determined in placental LZ samples (representative for each sex and genotype) using western blotting as previously described [1,34]. Briefly, proteins were extracted using RIPA buffer (Thermo Fisher Scientific, USA) supplemented with Mini EDTA-free protease inhibitor cocktail mix (Roche, CH).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Immune priming begins in utero with the mother and can be linked to increased Bifidobacterium over the course of pregnancy. Supplementation of germ-free dams with Bifidobacterium breve UCC2003 is associated with transcriptional and morphological changes in the placenta and foetal compartments, including alterations of foetal liver immune pathways 208 . Other studies in humans have also indicated that maternal diet, such as fibre, and microbiome shape immune factors in cord blood, being associated with cord blood IgA 209 .…”
Section: Modulation Of Early-life Priming Of the Immune Systemmentioning
confidence: 99%